THOMAS LUCKMANN: KONTRIBUSI SOSIOLOGI PENGETAHUAN DALAM STUDI ISLAM - Lathifah Lathifah Munawaroh (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2022)
The reality of everyday life is considered to present itself as a reality par excellence. The reality is a social fact, is externally general and has the power to force the consciousness of each individual, because it is outside the individual and is in the social order. While knowledge means the belief that a phenomenon is real and has certain characteristics, namely reality that is present in the consciousness of the individual, so this knowledge is subjective. Luckmann uses the dialectical process experienced by the human through three moments; externalization, objectivization, and internalization. These moments do not always take place in a sequence of time, but they are simultaneously characterized by the three moments. The key to this theory of the construction of reality is influenced by Hegel's dialectic. From this it is known that the sociology of knowledge, especially in the theory of social construction is not a new offering of Berger and Luckmann, but this theory is a development of pre-existing theories. This social construction theory plays an important role in dialogue with Indonesian traditions in Islamic studies, especially when talking about the Islamic Law, so that Islamic Law with a sociological approach, especially with social construction theory will keep the jargon Islamic law as “sholihun likulli zamanin wa makanin” will be realized.